Can self-set goals encourage resource conservation?: Field experimental evidence from a smartphone app - Löschel, Andreas; Rodemeier, Matthias; Werthschulte, Madeline (European economic review, 2023)
This study leverages a large RCT to examine the potential of goal-setting nudges to encourage resource conservation at scale. We randomize a feature t…